(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The aim of this study is to evaluate the outcomes of various surgical methods for correcting CoA in different age categories and to determine the most appropriate surgical techniques that minimize complications such as recoarctation, left ventricular dysfunction, and paradoxical hypertension.